Relative phase measures of intersegmental coordination describe motor control impairments in children with cerebral palsy who exhibit stiff-knee gait. (November 2018) - Carollo, James J.; Worster, Kate; Pan, Zhaoxing; Ma, Julie; Chang, Frank; Valvano, Joanne
Abstract: Background: The purpose of this retrospective study was to explore lower limb intersegmental coordination as a clinically important indicator of motor control mechanisms in individuals with cerebral palsy exhibiting stiff-knee gait. We used the relative phase of thigh and foot segments around foot-off to describe motor control, given the relevance of the pre-swing phase of gait to the existence of stiff-knee gait. Methods: Traditional gait parameters and thigh/foot intersegmental coordination were calculated using pre-and postoperative kinematic data from a cohort of 54 subjects (92 legs) with spastic cerebral palsy. All participants had stiff-knee gait, walked without assistive devices, and underwent rectus femoris transfer surgery to improve swing period knee flexion. Analyses included correlations between a) preoperative intersegmental coordination and gait variables (knee flexion range, rate and gait performance) and b) pre-to-postoperative intersegmental coordination change and change in gait variables. Findings: Thigh/foot intersegmental coordination significantly ( P  < 0.001) correlated with knee flexion range, rate and walking speed. Postoperative intersegmental coordination was significantly more uncoupled than preoperative. Pre-to-postoperative intersegmental coordination improvement also significantly correlated with improvements in knee flexion range, rate and walking speed. Pre-to-postoperative changes in intersegmental coordination accounted for 43% and 36% of variance in knee flexion range change and knee flexion rate change respectively. Interpretation: Intersegmental coordination is a clinically important factor in knee flexion limitations associated with stiff-knee gait for individuals with cerebral palsy. These findings are a foundation for further study of intersegmental coordination measures as complements to traditional instrumented gait analysis. Highlights: Intersegmental coordination (ISC) is a descriptor of synergistic vs. selective movement patterns in CP. Relative phase measures facilitate analysis of ISC of adjacent and non-adjacent segments during gait. Stiff-knee gait (SKG) in CP is characterized by significantly greater synergistic thigh/foot ISC than typical. Thigh/foot ISC correlates with walking speed and knee flexion range and rate. ISC may explain post-surgical variability of rectus femoris transfer in CP.